Sap flow study on two different diameter sizes of Tectona grandis - Marryanna Lion,; Siti-Aisah Shamsuddin,; Wan Mohd Shukri Wan Ahmad, (Penerbit Universiti Kebangsaan Malaysia, 2017)
Sap flow pattern of Tectona grandis planted at lowland forest assessed. This study aimed to determine the sap movement of two different diameter sizes T. grandis. Two sizes selected were 16 and 38 cm in diameter at breast height (dbh). Sap flow meter (SFM) used to assess the sap velocity rates at the interval of 30 min within 24 h for 15 days. Diurnal sap flow of T. grandis shows that mean velocity is high during day time compared night time. Small diameter has high sap flow compared to that of bigger diameter. A flow rates was high at the inner layer and less at outer layer for smaller tree. The variation was vice versa when the tree was getting bigger. Variations in sap flow of T. grandis characterized by several environmental factors. It was found that size contribute in the differed sap flow of T. grandis.